Neuropsychological functioning of individuals with coca paste use disorder - Vergara-Moragues, Esperanza; Acosta Barreto, M.R.; Santiago-Ramajo, Sandra; Rivera, D; Pardo Pachón, J.A; González-Saiz, Francisco; Arango-Lasprilla, JC (Taylor and Francis Ltd., 2022)
Background: Cocaine use has increased worldwide in recent years. However, the specific effects of smoking coca paste and its consequences on the cognitive functioning of individuals are unknown. The purposes of this study were to compare the neuropsychological functioning of a group of 163 individuals with coca-paste use disorder (CPUD) to that of a group of 162 healthy controls (HC) and to examine the relationship between cognitive performance and sociodemographic characteristics of these groups. Methods: Participants were administered a comprehensive neuropsychological battery that included tests of learning and memory, language and executive functions. Results: Although there were no significant differences in age and educational level between the groups, individuals with CPUD had significantly lower cognitive performance on the tests of learning and memory, language and executive functions compared with HC. An interaction effect was observed between group (CPUD versus HC) and educational level in the cognitive domains of learning and memory and language, such that more years of education was associated with better performance in these domains only in the HC. Conclusions: Deficits in learning and memory, language and executive functions are common in individuals with CPUD. Cognitive rehabilitation programs have been shown to improve these functions in individuals with CPUD. Therefore, this study reinforces the necessity of including such programs as part of the holistic intervention plan for these individuals. © 2020 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: addiction; executive function; language; learning; memory; neuropsychological assessment; Scopus; JCR